Effect of rotary electromagnetic stirring during solidification of In-situ Al-TiB2 composites - Agrawal S.; Ghose A.K.; Chakrabarty I. (My University, 2025)
Al-TiB2 in-situ metal-matrix composite has been synthesized by reaction with commercially pure molten aluminum and potassium hexafluoro titanate (K2TiF6) and potassium tetrafluoro borate (KBF4) adopting stir casting method. Varying amounts of salts based on stoichiometric calculations were added to obtain 0, 5 and 8 wt.% of TiB2 in the composites. The melts were allowed to solidify with or without electromagnetic stirring in a rotary magnetic field. The effects of varying percentage of TiB2 reinforcements and magnetic stirring have been characterized by microstructural evolution and consequent improvement in mechanical properties. The application of rotary electromagnetic stirring (EMS) during solidification has shown very prominent effect on the aluminum matrix and the morphology of TiB2 particles and the consequent mechanical properties like hardness, tensile strength, and dry sliding wear resistance. © 2016 Elsevier Ltd